Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.ebiom.2018.11.066
|View full text |Cite
|
Sign up to set email alerts
|

FOXP1 negatively regulates tumor infiltrating lymphocyte migration in human breast cancer

Abstract: BackgroundFOXP1, a transcriptional regulator of lymphocyte development, is abnormally expressed in some human tumors. This study investigated FOXP1-mediated regulation of tumor infiltrating lymphocytes (TIL) in untreated primary breast cancer (BC).MethodsFOXP1 expression was analyzed in tissues from primary untreated breast tumors, BC cell lines and the METABRIC gene expression BC dataset. Cytokine and chemokine expression and lymphocyte migration in response to primary tumor supernatants (SN) was compared bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 51 publications
(82 reference statements)
5
33
0
Order By: Relevance
“…This is also consistent with T-cell activation signatures being affected by FOXP1 silencing in human DLBCL cell lines (9). It is also possible that Foxp1 depletion may improve lymphocyte migration into the tumor microenvironment, as is the case in breast cancer where FOXP1 has recently been identified as a negative regulator of tumor infiltrating lymphocyte migration (43). However, preliminary ex vivo immunohistochemical analysis of harvested A20 tumors only found reduced numbers of CD3 + and CD8 + T cells in the Foxp1 exon 7 targeted tumors (data not shown), suggesting that reduced T-cell infiltration may not explain the common phenotype shared by both A20 clones.…”
Section: Discussionsupporting
confidence: 79%
“…This is also consistent with T-cell activation signatures being affected by FOXP1 silencing in human DLBCL cell lines (9). It is also possible that Foxp1 depletion may improve lymphocyte migration into the tumor microenvironment, as is the case in breast cancer where FOXP1 has recently been identified as a negative regulator of tumor infiltrating lymphocyte migration (43). However, preliminary ex vivo immunohistochemical analysis of harvested A20 tumors only found reduced numbers of CD3 + and CD8 + T cells in the Foxp1 exon 7 targeted tumors (data not shown), suggesting that reduced T-cell infiltration may not explain the common phenotype shared by both A20 clones.…”
Section: Discussionsupporting
confidence: 79%
“…69). Our laboratory recently demonstrated that the transcription factor FOXP1 is an important negative regulator of immune cell migration in BC via its impact on tumor cell cytokine and chemokine expression (70). Further, we found that CXCL13-producing T FH (named T FH X13) TIL promote local memory TIL-B differentiation and are potentially an early trigger of TLS formation in BC (12).…”
Section: Discussionmentioning
confidence: 89%
“…Forkhead Box P1 (FOXP1) belongs to the forkhead box transcription factor family, and has known to have dual roles as a tumor suppressor gene and as an oncogene in multiple cancer types [64,65]. FOXP1 deletions are found in squamous cell carcinomas of the lung, and expression of FOXP1 is associated with breast cancer development in poor prognosis in patients [4,64,66].…”
Section: Discussionmentioning
confidence: 99%